THE EFFECT OF LOADING ON THE LIFETIME OF A 50 KV DISTRIBUTION TRANSFORMER ON THE LMS01 FEEDER IN TAMBAKREJA VILLAGE, ULP CILACAP CITY - Biandi Bagas Saputra, Wim; Kholistianingsih; Darmawan, Isra' Nuur; Dharma Sukowati, Irawan (Program Studi Teknik Elektro Universitas Peradaban, 2025)
This Study Aims To Analyze The Effect Of Loading On The Life-Time Of A 50 Kv Distribution Transformer at Penyulang LMS01, Tambakreja Village, ULP Cilacap Kota. Distribution transformers are critical components in power systems, and overloading can accelerate performance degradation and reduce their lifespan. The research method involves measuring current, voltage, and load power of a B&D transformer from 2019 to 2023. The analysis reveals that excessive loading, especially during nighttime, reduces the transformer's lifespan by 8 years and 9 months from the standard 20 years, with an error value of 44,25%. The remaining lifespan is estimated at only 11 years and 3 months. This study recommends regular monitoring and limiting loads to below 80% capacity to extend the transformer's operational life.